Changes in physicochemical properties of beef in different age groups during short-term aging under chilled conditions - Bristy, MK; Mostafa, MS; Juthi, JF; Mahbub, MM; Badhan, SJ; Nahar, S; Murshed, HM (Meat Research, 2025)
This study examined the physico-chemical properties of beef from two age groups of Holstein Friesian crossbred bulls, specifically 15-month-old and 2-year-old, during a 5-day chilling aging process. The aim was to evaluate how aging affects various meat quality parameters, including pH, water holding capacity (WHC), drip loss, color, crude protein (CP), dry matter, ash, cooking loss, and shear force. Results showed significant differences between the two age groups. The 2-year-old beef had a higher initial pH and better water holding capacity compared to the 15-month-old beef, which experienced greater drip loss. Color analysis indicated that 2-year-old beef displayed a more vibrant red hue, enhancing its visual appeal. Additionally, the crude protein content was higher in the older cattle, although dry matter content was not significantly different. Cooking loss (20.20%) and shear force measurements demonstrated that 2-year-old beef was more tender, which correlated with superior water retention and less age-related connective tissue development. The aging process significantly influences (P<0.01) beef quality parameters, including water holding capacity (WHC), drip loss, tenderness, pH, and cooking loss. Using beef samples (T1=1 year 3 months and T2=2 years), subjected to aging periods of 1 day, 3 days, and 5 days, a comprehensive analysis assessed changes in WHC, drip loss, tenderness, pH, and cooking loss over time. WHC, drip loss, pH, cooking loss, and shear force showed minimal changes throughout aging, though an improvement in WBSF value (36.98 N) was noted with longer aging. Importantly, no significant changes were observed in meat quality attributes within this timeframe, indicating that the chilling process effectively preserved the samples’ integrity. Both age groups showed improvements in texture and tenderness, suggesting that a chilling temperature of 4°C may be optimal for promoting these desirable qualities.